The Korean vegan : homemade : recipes and stories from my kitchen - Lee Molinaro, Joanne (Avery, an imprint of Penguin Random House, 2025)
"Joanne Molinaro is everyone's favorite storytelling vegan cook. On her platform, The Korean Vegan, she's known for her personal narrative voiceovers, which accompany mouthwatering videos of her making everything from Kimchi to Korean-inspired pasta dishes. Whether it's a reflection on her relationship with her father over a plate of noodles or a story about learning to love her body as a marathon runner while she bakes dessert, Joanne is always making deep connections with her followers through food. Now, in The Korean Vegan: Homemade, Joanne offers the recipes that she makes most often at home. As Joanne likes to say, she loves to "veganize" Korean cuisine and "Koreanize" everything else. This book is a tribute to all the food influences that have shaped her cooking over the years and incredible flavors they have created. A memory about learning to repurpose leftover rice from her grandmother Hahlmuhnee results in Fried Rice Waffles; a question from her father leads to Joanne learning to make his childhood favorite noodles, Janchi Guksu; her Pesto Tteokbokki combines her husband's Italian roots with her own; and her love of savory snacks and kimchi helps invent Buffalo Kimchi Artichoke Dip. With her stunning signature photography and tips for building a Korean pantry, Joanne celebrates the magical connections between family, home, and food"--